2007
DOI: 10.1002/mrdd.20175
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary effects of parenting and stress management interventions for parents of children with developmental disabilities: A meta‐analysis

Abstract: A meta-analysis of the group intervention research for parents of children with developmental disabilities was conducted in order to characterize the efficacy of treatments in reducing depressive symptoms and other forms of psychological distress associated with stress in parents of children with developmental disabilities. An extensive search led to the identification of 17 studies which were divided into three categories for comparative purposes: parenting education studies usually based on behavioral parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(178 citation statements)
references
References 51 publications
8
156
3
6
Order By: Relevance
“…Data from multiple studies reveal that families who participate actively in problem-solving and stress management have more positive outcomes [e.g., Kim et al, 2003]. Singer et al [2007] conducted a meta-analysis of established parenting and stress management interventions for parents of children with developmental disabilities. This informative study revealed, among other findings, that multiple component interventions addressing both parental well-being and behavioral parent training were clearly more effective than either parent training or cognitive behavioral training alone.…”
Section: Interventions For Families Raising Children With Developmentmentioning
confidence: 99%
“…Data from multiple studies reveal that families who participate actively in problem-solving and stress management have more positive outcomes [e.g., Kim et al, 2003]. Singer et al [2007] conducted a meta-analysis of established parenting and stress management interventions for parents of children with developmental disabilities. This informative study revealed, among other findings, that multiple component interventions addressing both parental well-being and behavioral parent training were clearly more effective than either parent training or cognitive behavioral training alone.…”
Section: Interventions For Families Raising Children With Developmentmentioning
confidence: 99%
“…We are aware of one meta-analysis that examined treatments for parents of children with various developmental disabilities, but which included children diagnosed with developmental disabilities (nonspecified), intellectual disabilities, traumatic brain injury, as well as autism (Singer, Ethridge, & Aldana, 2007). Out of the 17 studies reviewed, only four investigated interventions designed exclusively for parents of children with an ASD diagnosis (Bristol et al, 1993;Drew et al, 2002;Salt et al, 2002;Tonge et al, 2006).…”
mentioning
confidence: 99%
“…The effect size in 17 study literatures on the parenting stress in parents of children with disabilities was confirmed to be strong with.08 (Cohen, 1977), which was lower than the effect size of -1.84 in the previous meta-analysis on the parenting stress in parents of children with disabilities in Korea (Yi, 2014) but higher than the size of -0.49 in an overseas study on the control of parenting and stress in the parents of children with developmental disorders (Singer et al, 2007). We thus learned that Korean experimental studies were quite effective in controlling parenting stress.…”
Section: Discussionmentioning
confidence: 55%